The immunoregulatory role of helper T cells in Helicobacter pylori infection - Wu, Xianli; Gou, Guoyou; Wen, Min; Wang, Fang; Liu, Youjia; Li, Lingli; Xu, Jingyu; Xie, Rui (Frontiers in Immunology, 2025)
Helicobacter pylori (H. pylori) is a pathogenic bacterium that can survive in the human gastric mucosa and cause chronic infections. More than half of the global population is affected by H. pylori infection, which is closely associated with the development of gastritis, gastric ulcers, gastric cancer, and mucosa - associated lymphoid tissue lymphoma. The immune response triggered by H. pylori infection is complex and involves multiple immune cells. Among them, helper T cells (Th cells) play a crucial role in regulating the immune response. In recent years, researchers have conducted in - depth explorations of the immunoregulatory mechanisms, pathological effects of Th cells in H. pylori infection, and their applications in treatment. However, there are still problems such as insufficient understanding of the functions of Th cell subsets and unclear clinical treatment strategies. This paper aims to review the immunoregulatory role of Th cells in H. pylori infection, analyze their mechanism of action in the pathological process, and explore the future research directions and the development of treatment strategies, providing a theoretical basis for research in this field.